The Effect of Irrigation on Crop Yield Change in Some Cereals in Drought Conditions Determined Using SPI and PNI: Ankara Province Example - Murat Özocak (Turkish Journal of Agriculture: Food Science and Technology)
In this study, Standard Precipitation Index (SPI) and Percent of Normal Index (PNI) values were found in order to determine the drought conditions between 2012-2020 in Ankara province. Drought severity interpretations were made according to the index values obtained and these values were evaluated together with some grain yields grown in the region. Separate regression analysis was performed between the different drought index values obtained within the scope of the study and the irrigated and dry agricultural yield values of wheat, barley and triticale. According to the index values calculated between 2012 and 2020 according to the SPI method, drought conditions are generally close to normal in the region. According to the PNI values, it was determined that 2013 had mildly dry conditions and other years had near-normal drought conditions. According to both indices, a drought close to normal was observed during the research period. In the regression analysis made according to wheat, barley and triticale yields, the highest linearity was obtained in barley, and values close to barley were found in triticale. Wheat is the cereal with the lowest linearity. The regression coefficients obtained as 0.4294 for barley, 0.3331 for triticale, and 0.0502 for wheat were found to be 0.0584 for SPI and 0.0013 for PNI. According to the results obtained, it can be said that statistically linearity is in barley and triticale. In average yields, an increase of 47% in wheat, 55% in barley and 34% in triticale was observed with irrigation. In order to ensure sustainable grain cultivation in drought conditions, it is recommended to expand modern irrigation practices in coordination with drought analysis studies and to increase scientific studies on this subject.